Methods of studying the composition of the low-energy ion beams and the surface of deuterated-metal targets; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Kuznetsov S. I. Sergey Ivanovich; Dudkin G. N. Gennadiy Nikolaevich; Nechaev B. A. Boris Aleksandrovich; Bystritsky I. D. (2016, 2016)
Title screen